Recurrent Gastrointestinal Stromal Tumors in the Imatinib Mesylate Era: Treatment Strategies for an Incurable Disease. (30th November 2017) - Platoff, Rebecca M.; Morano, William F.; Marconcini, Luiz; DeLeo, Nicholas; Mapow, Beth L.; Styler, Michael; Bowne, Wilbur B.
Abstract : Introduction . Recurrence of gastrointestinal stromal tumors (GISTs) after surgical resection and imatinib mesylate (IM) adjuvant therapy poses a significant treatment challenge. We present the case of a patient who underwent surgical resection after recurrence and review the current literature regarding treatment. Case Presentation . A 58-year-old man with a large intra-abdominal jejunal GIST was treated with complete surgical resection followed by IM. The patient experienced disease recurrence 3.5 years later and underwent IM dose escalation and reresection. Conclusion . Current strategies to treat recurrent GIST include dose escalation, modifying adjuvant tyrosine kinase inhibitor therapy, and surgery. High-level evidence will be required to better define the combinatory roles of tyrosine kinase inhibitor therapy, guided by molecular profiling, and surgery in the management of recurrent GIST.